Intact O-antigen is critical structure for the exceptional tubular shape of outer membrane vesicles in Francisella tularensis - Bavlovic, Jan; Pavkova, Ivona; Balonova, Lucie; Benada, Oldrich; Stulik, Jiri; Klimentova, Jana (Microbiological research, 2023)
Francisella tularensis is a highly infectious Gram-negative coccobacillus which causes the disease tularemia. The potential for its misuse as a biological weapon has led disease control and prevention centers to classify this bacterium as a category A agent. Bacterial outer membrane vesicles (OMVs) are spherical particles 20-250 nm in size produced by all Gram-negative bacteria and constitute one of the major secretory pathways. Bacteria use them in interacting with both other bacterial cells and eukaryotic (host) cells. OMVs of Francisella contain number of its so far described virulence factors and immunomodulatory proteins. Their role in host-pathogen interactions can therefore be presumed, and the possibility exists also for their potential use in a subunit vaccine. Moreover, Francisella microbes produce both usual spherical and unusual tubular OMVs. Because OMVs emerge from the outermost surface of the bacterial cell, we focused on the secretion of OMVs in several mutant Francisella strains with disrupted surface structures (namely the O-antigen). O-antigen in Francisella is not only the structural component of LPS but also forms another important virulence factor: the O-antigen polysaccharide capsule. Mutant strain phenotypes were evaluated by growth curves, vesiculation rates, their sensitivity to the complement contained in serum, and proliferation inside murine bone marrow macrophages. Morphologies of both OMVs and the bacteria were visualized by electron microscopy. The O-antigen mutant strains were considerably attenuated in serum resistance and intracellular proliferation. All the strains showed lower ability to form the tubular OMVs. Some strains formed tubular protrusions from their outer membrane but their stability was weak. Some hypervesiculating strains were revealed that will serve as source of OMVs for further studies of their protective potential. Our results suggest the presence of LPS and the O-antigen capsule on the surface of Francisella to be critical not only for its virulence but also for the exceptional tubular shape of its OMVs.
Keywords: O Antigens; tularemie; Animals; O-antigeny; Bacterial Outer Membrane Proteins; Gram-Negative Bacteria; gramnegativní bakterie; zvířata; Francisella tularensis; lipopolysacharidy; Mice; proteiny vnější bakteriální membrány; Tularemia; Lipopolysaccharides; myši